Edukasi Kesehatan Tentang Penyakit Diabetes Melitus bagi Masyarakat - Aminuddin, Aminuddin; Sima, Yenny; Cholifatul Izza, Nurril; Syamsi Norma Lalla, Nur; Arda, Darmi (Lembaga Penelitian dan Pengabdian Masyarakat,Politeknik Sandi Karsa, 2023)
Background: Diabetes mellitus is a chronic disease that occurs when the pancreas cannot produce enough insulin or the body cannot use the insulin produced effectively. Insulin is a hormone that regulates blood sugar. Purpose of service: To provide health education about diabetes mellitus for the community. Method: This service activity is carried out through direct observation of the community and dor to dor education. Results show that counseling can increase the knowledge of each Pretest by 48% and Posttest by 78%. Conclusion: Their knowledge is also increased by providing health education to the public. This community service activity can have an impact on improving the degree of public health.